Ticks and Tick-Borne Pathogens in Domestic Animals, Wild Pigs, and Off-Host Environmental Sampling in Guam, USA - Weaver, Genevieve V.; Anderson, Neil; Garrett, Kayla; Thompson, Alec T.; Yabsley, Michael J. (Frontiers in Veterinary Science, 2022)
Background: Guam, a United States of America (USA) island territory in the Pacific Ocean, is known to have large populations of ticks; however, it is unclear what the risk is to wildlife and humans living on the island. Dog (Canis familiaris), cat (Felis catus), and wild pig (Sus scrofa) sentinels were examined for ticks, and environmental sampling was conducted to determine the ticks present in Guam and the prevalence of tick-borne pathogens in hosts. Methods and Results: From March 2019-November 2020, ticks were collected from environmental sampling, dogs, cats, and wild pigs. Blood samples were also taken from a subset of animals. A total of 99 ticks were collected from 27 environmental samples and all were Rhipicephalus sanguineus, the brown dog tick. Most ticks were collected during the dry season with an overall sampling success rate of 63% (95% CI: 42.4–80.6). 6,614 dogs were examined, and 12.6% (95% CI: 11.8–13.4) were infested with at least one tick. One thousand one hundred twelve cats were examined, and six (0.54%; 95% CI: 0.20–1.1) were found with ticks. Sixty-four wild pigs were examined and 17.2% (95% CI: 9.5–27.8) had ticks. In total, 1,956 ticks were collected and 97.4% of ticks were R. sanguineus. A subset of R. sanguineus were determined to be the tropical lineage. The other tick species found were Rhipicephalus microplus (0.77%), Amblyomma breviscutatum (0.77 %), and a Haemaphysalis sp. (0.51%). Blood samples from 136 dogs, four cats, and 64 wild pigs were tested using polymerase chain reaction (PCR) and DNA sequencing methods. Five different tick-borne pathogens with the following prevalences were found in dogs: Anaplasma phagocytophilum 5.9% (95% CI: 2.6–11.3); Anaplasma platys 19.1% (95% CI: 12.9–26.7); Babesia canis vogeli 8.8% (95% CI: 4.6–14.9); Ehrlichia canis 12.5% (95% CI: 7.5–19.3); Hepatozoon canis 14.7% (95% CI: 9.2–28.8). E. canis was detected in one cat, and no tick-borne pathogens were detected in wild pigs. Overall, 43.4% (95% CI: 34.9–52.1) of dogs had at least one tick-borne pathogen. Serological testing for antibodies against Ehrlichia spp. and Anaplasma spp. showed prevalences of 14.7% (95% CI: 9.2–28.8) and 31.6% (95% CI: 23.9–40), respectively. Conclusion: Four different tick species were found in Guam to include a Haemaphysalis sp., which is a previously unreported genus for Guam. Dogs with ticks have a high prevalence of tick-borne pathogens which makes them useful sentinels.